2001
DOI: 10.1007/s11746-001-0361-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and surface and biological properties of N‐stearoyl amino acids

Abstract: Several lipoamino acids were synthesized, in which n-octadecanoic acid (stearic acid) was coupled with the α-amino group of an amino acid. The products were characterized and their identities confirmed by advanced analytical techniques like Fourier transform infrared, 1 H nuclear magnetic resonance spectroscopy, and differential scanning calorimetry. Their surface properties, such as critical micelle concentration (CMC) and foaming properties, biodegradability, and antimicrobial activity were also evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Similar phenomenon occurred to the dipeptide of leucine and aspartic acid in which aspartic acid is on the C-terminal position ( 37 ). The mechanism is shown in the supplementary data.…”
Section: N -Stearoyl Tyrosine (Supplementary Data) the Anions [Rcoo]supporting
confidence: 57%
“…Similar phenomenon occurred to the dipeptide of leucine and aspartic acid in which aspartic acid is on the C-terminal position ( 37 ). The mechanism is shown in the supplementary data.…”
Section: N -Stearoyl Tyrosine (Supplementary Data) the Anions [Rcoo]supporting
confidence: 57%
“…Proton NMR spectral data showed peaks corresponding to protons of corresponding to double bond and protons adjacent to carbonyl at around 5.5 and 2.2 δ respectively for fatty acid along with amide proton at around 6.0-6.4 with the methylene proton in the amino acid moiety at around 4.6 δ. IR spectral data showed carbonyl peaks corresponding to both amide 1650 cm 1 and carboxylic acid 1710 cm 1 functionalities. The spectral data for characteristic peaks was observed to be in compliance to earlier reported data for the fatty amino acid conjugates 11,18 .…”
Section: Resultssupporting
confidence: 88%
“…These types of compounds have been reported to be biodegradable and have applications in food, pharmaceutical, medical and cosmetic fields 9 . Earlier reports on N-palmitoylated amino acids and N-stearyl amino acids showed that these types of compounds exhibited biological activities and could have applications as potential biostatic additives 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Sodium salts of N-acyl amino acids are well-known anionic surfactants with good biodegradability, skin compatibility and antibacterial activity [1][2][3][4][5][6][7][8][9] . Generally, they have been prepared from fatty acid chlorides and amino acids [10][11][12][13][14][15] , where acid halides are used to introduce the hydrophobic groups.…”
Section: Resultsmentioning
confidence: 99%